Differences in gastric microbiota and mucosal function between patients with chronic superficial gastritis and intestinal metaplasia - Li, Yingxia; Jiang, Libin; Li, Zhichao; Liu, Yali; Xiao, Bo; Ding, Yan; Wen, Hongtao (Frontiers in Microbiology, 2022)
Chronic superficial gastritis (CSG) and intestinal metaplasia (IM) can further develop into gastric cancer, which seriously endangers the health of people all over the world. In this study, the differences in gastric microbiota between CSG patients and IM patients were detected by 16S rRNA gene sequencing. As the expression levels of mucin and CDX2 are closely related to IM, the expression differences of mucin (MUC2 and MUC5AC) and CDX2 in the gastric mucosa of CSG patients and IM patients were detected by Western blot and qRT-PCR. The results showed that both Faith_pd and Observed_species indexes of microbiota in the gastric juice of CSG patients were significantly higher than those of IM patients. At the genus level, Thermus and Anoxybacillus were dominant in the gastric juice of IM patients, and Helicobacter was dominant in the gastric juice of CSG patients. Non-metric multidimensional scaling (NMDS) demonstrated that the dispersion of samples in the CSG group is greater than that in the IM group, and some samples in the CSG group are clustered with samples in the IM group. The KEGG metabolic pathway difference analysis of gastric juice microbiota in CSG and IM patients revealed that the gastric juice microbiota in the CSG and IM patients were significantly enriched in the amino acid metabolism, carbohydrate metabolism, and metabolism of cofactors and vitamins, and the functional differences between the two groups were mainly concentrated in the bacterial secretion system (VirB1, VirB2, VirB3, VirD2, and VirD4). In conclusion, there are significant differences in gastric microbiota and mucosal function between the CSG and IM patients. Moreover, the results of this study may provide a new means for the detection of CSG and IM and a new direction for the prevention and treatment of CSG and IM.